Islam in Ziya Gökalp's Positivist Thought: His Articles and Poems in the Journal of Islam - Remzi Soytürk (Turkish Academic Research Review)

(untitled)
Positivist thought, which became widespread in Europe in the second half of the 19th century, also had representatives in the Ottoman intellectual life after the Second Constitutional Monarchy. At the outset the Ottoman positivist literature begin with the famous letter written by Auguste Comte to the Ottoman Grand Vizier Mustafa Reşid Pasha in order to adopt the positivist philosophy. Although we include intellects such as Beşir Fuat, Ahmet Rıza and Rıza Tevfik, it is difficult to talk about a systematic positivist movement. Ziya Gökalp, one of the most important representatives of positivist thought in the Ottoman Empire, while following Durkheim, on the other hand, seeks to establish a unique sociology school. Using scientific sociological methods, Gökalp establishes a dialogue between Western civilization and Turkish culture and seeks solutions to the problems of the modernizing Ottoman society. While following the Western positivism as a method, Gökalp, the father of the nationalist and Turkist movement, is in search of a new national identity by incorporating national values, especially the religion of Islam, into his theories. In this context, Gökalp's model of society also differs from Durkheim's positivist thought at some points. According to Durkheim, based on the law of three stages of Auguste Comte, we passed the theological and metaphysical stage and finally came to the positivist stage. On the other hand, Gökalp does not completely exclude religion and thinks about the dominant role of Islam in the formation of the character of the individual and society. One of the best sources from which we can follow Gökalp's thoughts on this subject is the journal of the Committee of Union and Progress, the Journal of Islam. While Gökalp tried to solve the problems between fiqh and sociology with a new method he called “social fiqh” in his articles published in this journal; in his poems, he describes the place of religion in social and individual life in a style that is far from poetic. Claiming that we are living in "the age of consciousness, not poetry", while conducting deep social discussions in his articles in the Journal of Islam, he uses divine themes in his poems in a plain language, away from aesthetic concerns, by associating them with social issues. This study is an attempt to examine the place of Islam in Ziya Gökalp's sociology through his articles and poems in the Journal of Islam.